IMPLEMENTASI PERATURAN DAERAH NOMOR 10 TAHUN 2022 TENTANG PENYELENGGARAAN PERIZINAN BERUSAHA BERBASIS ONLINE SINGLE SUBMISSION (OSS) DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN SUKOHARJO - Ratna Widyastuti, Anggraista; Suranto, Joko; Wirawan, Riska (Solidaritas, 2024)
The Government of the Republic of Indonesia is committed to encouraging businessgrowth and investment by launching Online Single Submission (OSS), LocalGovernments have an important role in ensuring that policies are implementedeffectively. The implementation of business licensing in Sukoharjo Regency is organizedby the One-Stop Investment and Integrated Services Office (DPMPTSP) with anelectronic basis through Online Single Submission (OSS). This study aims to describethe Implementation of Regional Regulation Number 10 of 2022 concerning theImplementation of Business Licensing Based on Online Single Submission (OSS) at theOne-Stop Investment and Integrated Services Office of Sukoharjo Regency. Thisresearch uses the theory of Policy Implementation George C. Edward III. This type ofresearch is descriptive qualitative, the types of data used are primary data andsecondary data, determining informants using purposive sampling techniques. The datacollection techniques used in this research are: observation, interviews anddocumentation. Data analysis techniques used are data collection, data condensation,data presentation and conclusion drawing. The results showed that the SukoharjoRegency Investment and One-Stop Integrated Service Office always tries to implementRegional Regulation Number 10 of 2022 concerning the Implementation of BusinessLicensing Based on Online Single Submission (OSS) properly. However, there are stillobstacles, namely in terms of communication, not fully providing understanding to thecommunity, including business actors who have not updated and migrated data to OSSRBA and even though the licensing system has been integrated online, there are stillmany applicants who come to the office. Bureaucratic Structure related to StandardOperating Procedures (SOP) there is already a service flow mechanism but RegionalRegulation Number 10 of 2022 does not explain the Standard Operating Procedures(SOP) regarding the implementation of business licensing based on Online SingleSubmission (OSS).Keywords: Implementation, Business Licensing, Online Single Submission (OSS)